Demonetization of Indian Economy: A Review on the Effects and Reactions (Indian Journal of Extension Education, 2019)
From slowing down the economic growth in various sectors to give people nightmares of the long queues and the inability to spend liquid cash freely, the hullabaloo created by demonetization is remembered by one and all. Demonetization was initiated with a wide array of motives like stripping the Indian economy of its black money, push people to pay taxes for the unaccounted pile of cash, curb terrorism, promote the digital India movement and make India a cashless economy. Demonetization, technically is a liquidity shock; a sudden stop in terms of currency availability. It creates a situation where lack of currencies jams consumption, investment, production, employment etc. In this context, the exercise may produce short term/long term/, consumption/ investment, welfare/growth impacts on Indian economy. The intensity of demonetization effects clearly depends upon the duration of the liquidity shocks. Demonetization is a generations’ memorable experience and is going to be one of the economic events of our time. Its impact is felt by every Indian citizen. Demonetization affects the economy through the liquidity side. Its effect will be a telling one because nearly 86 per cent of currency value in circulation was withdrawn without replacing bulk of it. As a result of the withdrawal of Rs 500 and Rs 1000 notes, there occurred huge gap in the currency composition as after Rs 100; Rs 2000 is and was the only denomination.